2004
DOI: 10.1029/2003ja009968
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of photometer and global MHD determination of the open‐closed field line boundary

Abstract: [1] We compare open-closed field line boundary positions from the BATS-R-US Global MHD model and CANOPUS photometer measurements of red-line emissions. We choose intervals of steady interplanetary and ionospheric conditions in order to adhere to the ''steady-state'' picture that we are trying to address. Nine intervals are chosen that correspond to stable IMF and auroral conditions that can be simulated with the MHD model. We find that on average, the steady-state BATS-R-US MHD model provides an excellent esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 25 publications
3
39
0
Order By: Relevance
“…[29] On the basis of previous work [Lanzerotti et al, 1999] and having shown that observations largely agree (∼83%) with output of the BATSRUS global magnetospheric model (previously established to accurately represent the OCB during quiet geomagnetic conditions [Rae et al, 2004]), we conclude that real-time determination of the OCB can be successfully accomplished with reasonable accuracy using an array of fluxgate magnetometers, as was demonstrated herein for the period 1-9 August 2008, using the PENGUIn-AGO array of fluxgate magnetometer instruments. The steady, repeatable features at the four network locations (shown in Figures 4-6) follow the gross features of the OCBpolar cap environment and make it possible to make more detailed studies of this environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[29] On the basis of previous work [Lanzerotti et al, 1999] and having shown that observations largely agree (∼83%) with output of the BATSRUS global magnetospheric model (previously established to accurately represent the OCB during quiet geomagnetic conditions [Rae et al, 2004]), we conclude that real-time determination of the OCB can be successfully accomplished with reasonable accuracy using an array of fluxgate magnetometers, as was demonstrated herein for the period 1-9 August 2008, using the PENGUIn-AGO array of fluxgate magnetometer instruments. The steady, repeatable features at the four network locations (shown in Figures 4-6) follow the gross features of the OCBpolar cap environment and make it possible to make more detailed studies of this environment.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of only the size of the polar cap inherently contains no site-specific information and thus is not useful in determining how the OCB varies azimuthally for a prescribed set of space weather parameters. Such precise site-specific information is crucial to many ongoing areas of research which include the investigation of reconnection rates at the magnetopause [Lockwood et al, 2005] and in the magnetotail [Milan, 2004], analyzing how the OCB synoptically transforms throughout the substorm cycle, and modeling the magnetospheric system more accurately [Tsyganenko, 1995;Pulkkinen and Tsyganenko, 1996;Rae et al, 2004;Gombosi et al, 2004].…”
Section: Ocb Diagnostics and Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular MHD codes have been compared against each other but, most importantly, reasonably well validated against a variety of in situ spacecraft and ground-based measurements [Janhunen et al, 1995;Fedder et al, 1998;Raeder et al, 1998;Winglee and Menietti, 1998;Gombosi et al, 1998;Raeder et al, 2001;Slinker et al, 2001;White et al, 2001;Siscoe et al, 2002;Kabin et al, 2003;Rae et al, 2004;Ohtani and Raeder, 2004;Nakata et al, 2004].…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…In this study, we were able to estimate the location of the open-closed separatrix via visual identification of the cutoff in red-line auroral emissions using the CANOPUS GILL meridian scanning photometer (not shown; e.g., Blanchard et al, 1995;Rae et al, 2004), and find that this boundary resides close, but equatorward, of the FCHU station. The largest time lag (which characterises the shortest time of flight) between the in-situ BBF flow bursts and the Pi2 observed along the Churchill Line on the ground is at PINA, deep within the closed field line region, rather than occurring at a station that maps to the reconnection site as proposed by Keiling et al (2006).…”
Section: Discussionmentioning
confidence: 99%